THE PORTRAIT OF AUTHENTIC MATERIAL IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) AT SMK NEGERI 2 CIREBON - Vianty Wulandari; Edy Waloyo (IAIN Syekh Nurjati Cirebon, 2018)
The aim of this research is to investigate teaching and learning English for Specific Purposes (ESP) at SMK Negeri 2 Cirebon using the authentic materials. The method which used in this research is descriptive qualitative research. The techniques of collecting data are observation, interview and document study to know the process of teaching and learning ESP using authentic materials. The population in this research is students of hotel accommodation program. The sample of this research was a hotel accommodation class and an English teacher. The validity data in this research are credibility, dependability, transferability and conformability. Credibility refers to triangulation data of the observation, interview transcriptions and documents. Dependability refers to parallels prove, transferability refers to study previous document and conformability refers to the research objectivity. The result of this research shows that the process using authentic materials in teaching ESP works good, because the teacher selected the authentic learning materials appropriately relevance with students’ needs and interests. Therefore, the teacher has positive response and the students also have the positive responses to the teaching and learning ESP using authentic materials. In this research, the researcher found good portrait of authentic materials toward teaching and learning ESP at hotel accommodation program and the positive response between teacher and students about teaching and learning ESP using the authentic material.Keywords: ESP, Authentic Materials, Teaching Speaking